Antibiotic Resistance in Urinary Tract Infection in a Tertiary Care Hospital in Bangladesh-A Follow-up Study (Medicine Today, 2019)
Introduction: Bacterial resistance to antibiotics is one of the most challenging global health threats. Urinary tract infections (UTIs) are a common infection. Regional surveillance programs are necessary to update knowledge on antimicrobial resistance pattern where empirical antibiotic treatment is the mainstay. The aim of this follow up study is to see the changing trends in bacteriology and antibiotic resistance pattern among urological pathogens in comparison to similar study 5 years back.Materials and Methods: We performed a prospective study in Comilla Medical College Hospital, Bangladesh during the period of July 2015- June 2016. Midstream clean-catch urine samples were collected from 658 suspected UTI patients with age more than 12 years and inoculated in MacConkey& Blood agar media for semi quantitative urine culture and sensitivity test. Antibiotic susceptibility pattern was done by Kirby-Bauer disc diffusion method following clinical laboratory science (CLS) program.Results: Culture positive were in 198 samples among 658 inoculated samples. E. coli was isolated from 171(86%) samples which was the most predominant bacteria followed by Klebsiella and Enterococcus. UTI with E. coli was significantly increased in the year 2016 in comparison to 2011. Meropenem, imipenem, amikacin, tazobactum, gentamycin nitrofurantoin, and mecillinum found resistance against 0% to 12% of the urological pathogens. Bacteria offered high degree of resistance against commonly used antibiotics - amoxycillin, amoxiclav, cephradine and cefixime ranging 60% to 86%. Comparative study of 2016 vs 2011 shows significant increased resistance for ceftriaxone, amoxiclav and reduced resistance for nalidexic acid, mecillinum and cefuroxime.Conclusion: E. coli infection is significantly increaseing in follow up study from 2011 to 2016 with no steady increase in resistance to all antibiotics. Imipenem, meropenem, tazobactum, amikacin and nitrofurantoin still remain more sensitive while comparative study of 2016 vs 2011 shows significant increased resistance for ceftriaxone, and amoxiclave and reduced resistance for nalidexic acid, mecillinum, cefixime and cefuroxime.Medicine Today 2019 Vol.31(1): 9-14